PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN LOKASI TERHADAP KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN JASA SERVIS MOBIL DI HONDA SOLO BARU - Legowo Dwi Resihono (Universitas Slamet Riyadi, 2020)
This research aims to determine and explain the effect of service quality, brand image and location on consumer decisions in using services at Honda Solo Baru, either partially or simultaneously. This study uses a quantitative approach. The sample of this study was 91 consumers of Honda Solo Baru car service using non-probability sampling methods and accidental sampling techniques. This research instrument used a questionnaire and analyzed using multiple regression analysis. The results of this study indicate that partially service quality and location variables do not affect consumer decisions, while brand image variables significantly influence consumer decisions. The results simultaneously indicate that the variables of service quality, brand image and location have a significant influence on consumer decisions. This research contributes to the New Solo Honda to further improve the quality of service and location to bring customers to the New Solo Honda.